(untitled) (Journal of Forensic Medicine & Toxicology, 2026)
Neck lesions are often interpreted as evidence of compressive force over the neck during forensic investigations. However, corrosive chemical burns can create a deceptive appearance that closely resembles a ligature mark, potentially leading to misclassification of the manner of death. We report the case of a 68-year-old male found dead at home with band-like lesions on the neck, initially suspected to represent ligature strangulation. This case highlights how corrosive poisoning can mimic external signs of strangulation, misleading investigators toward homicide. Careful autopsy, histopathology, and toxicological confirmation were crucial in establishing the true cause and manner of death. Awareness of such mas querades is vital to avoid misinterpretation in forensic practice.